Lactic-acid bacteria increase the survival of marine shrimp, Litopenaeus vannamei, after infection with Vibrio harveyi - Vieira,Felipe do Nascimento (2007)
This study evaluated the survival, post-larvae quality, and the population of bacteria in Litopenaeus vannamei after the addition of two strains of lactic-acid bacteria (2 and B6) experimentally infected by Vibrio harveyi. Fifteen hundred nauplii were distributed in 20 L capacity tanks with four replicates. The survival of control animals was lower (21%) than that of animals fed with the strains B6 (50%) and 2 (44%). Total bacterial population in the water and larvae, as well as of the Vibrio ssp. in water was not different among the treatments. No difference was observed in the population of Vibrio ssp. between the control larvae (5.5±0.5 log UFC/mL) and that fed with strain 2 (5.4±0.1 log UFC/mL). Shrimp from control and fed with strain 2 showed significantly higher bacterial population than those fed with strain B6 (1.2±0.2 log UFC/mL). It was detected the lower load of Vibrio ssp. bacteria with potential of pathogenicity after feeding with strain B6.Moreover, these larvae showed more active behavior and low number of necrosis in relation to the control group and to that fed with strain 2.